Defining a Continuous Glucose Baseline to assess the impact of nutritional interventions - Chkroun, Célina; Trouwborst, Inez; Cherta-Murillo, Anna; Owen, Lauren; Darimont, Christian; Rytz, Andreas (Frontiers in Nutrition, 2023)
Accurate and robust estimation of individuals’ basal glucose level is a crucial measure in nutrition research but is typically estimated from one or more morning fasting samples. The use of Continuous Glucose Monitoring (CGM) devices presents an opportunity to define more robust basal glucose levels, which estimates can be generalized to any time of the day. However, to date, no standardized method has been delineated. The current paper seeks to define a reliable algorithm to characterize the individual’s basal glucose level over 24h from CGM measurements. Data drawn from four nutritional intervention studies performed on adults free from chronic diseases were used to define that basal glucose levels were optimally estimated using the 40th percentile of the previous 24 hours CGM data. This simple algorithm provides a Continuous Glucose Baseline over 24h (24h-CGB) that is an unbiased and highly correlated estimator (r=0.86, p-value<0.01) of standard fasting glucose. We conclude that 24-CGB can provide reliable basal glucose estimates across the day while being more robust to interference than standard fasting glucose, adaptable to evolving daily routines and providing useful reference values for free-living nutritional intervention research in non-diabetic individuals.